Effect of total knee arthroplasty on other joints in patients with rheumatoid arthritis evaluated by 18‐FDG‐PET. (16th March 2016) - Yonemoto, Yukio; Okamura, Koichi; Kaneko, Tetsuya; Okura, Chisa; Kobayashi, Tsutomu; Suto, Takahito; Tsushima, Yoshito; Takagishi, Kenji
Abstract: Aim: The objective of this study was to assess arthritis of the whole body before and after total knee arthroplasty (TKA) in patients with rheumatoid arthritis (RA) using positron emission tomography (PET). Method: Seventeen knees of 17 RA patients (median age 68 years) who underwent TKA were included in this study. Clinical assessments of disease activity, knee function and activities of daily living (ADL) were performed before and after TKA. 18 Fluorodeoxyglucose (FDG)‐PET was performed preoperatively and 12 weeks postoperatively when RA disease activity was assessed. The maximal standardized uptake value (SUV) in the region of interest was used to assess FDG uptake. Results: Disease activity and knee function improved in all patients after TKA. There was a significant decrease in the number of patients with swollen or tender joints involving the right wrist, right knee and left knee. The SUV of bilateral wrist joints decreased significantly 12 weeks after TKA, whereas the SUVs of other large joints were unchanged. Conclusion: TKA can improve not only ADL and knee function, but also the disease activity index in RA patients. However, TKA has limited effectiveness against synovitis of the joints not undergoing surgery.